Push and Pull Factors Influencing Destination Satisfaction For Sustainable Cultural Heritage Tourism Business Model: The Case Of Intramuros - Eunice Mareth Querol Areola, Phd HSG; Fernando Trinidad III (Journal of Sustainable Community Development (JSCD), 2022)
Intramuros is one of the country’s acknowledged premier Cultural Heritage Tourism (CHT) destination site. With the objective of formulating a CHT model toward destination satisfaction and loyalty, the study assessed its destination attributes from the perspectives of the visitors through the PUSH and PULL Framework. It employed a mixed quantitative and qualitative methods using a researcher-made survey questionnaire administered using purposive sampling to 305 visitors. The findings were also examined and justified through a Focused Group discussion (FGD) among different tour operators within the Intramuros area. Intramuros CHT visitors are predominantly female, young; single; living within Metro Manila; with income up to P500,000 and below; Bachelor’s Degree holder and student/employee or professional; has visited it more than once together with friends, partner and family; for holiday and leisure and family togetherness; and came to know of Intramuros through the Internet and word of mouth; with trip of less than 24 hours; using either his personal car or public transport as mode of transportation. The push factor of “seeking relaxation” and the pull factor of “Cultural Heritage Features” had the strongest influence on levels of satisfaction accounting for 90 per cent of the visitors who signified their intention to go back and recommend the site to other tourists; although there are significant differences of level of satisfaction among them when they are grouped according to their profile.The study found moderate and positive relationships between push and pull factors and the attributes of the heritage site and the overall satisfaction of the visitors. Findings of the study were used to craft a Cultural Heritage Tourism Business Model for Customer Satisfaction and Customer Loyalty for Intramuros.